MINAT KUNJUNG PEMBACA DITINJAU DARI DESAIN INTERIOR DAN KOLEKSI BUKU DI PERPUSTAKAAN PERGURUAN TINGGI - Edhy Rustan; Yonsen Fitrianto; Mardi Takwim (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: This study aims to examine the relationship between interior design, book collections, and readers' interest in visiting the university library. This research approach uses a quantitative paradigm with a correlational method. This study is to measure the relationship between interior design variables (X1), library book collections (X2), and interest in visiting readers (Y). The population of 2,802 was drawn in the sample to 97 through the multistage sampling technique. Data collection instruments, using observations, questionnaires, and documentation. The research data were analyzed using SPSS version 20 software to provide an overview of simple correlations and multiple correlations. The results showed that the interior design of the IAIN Palopo Library was excellent (93.4%), the book collection was in a reasonably good category (66.7%), and the interest in visiting students at the IAIN Palopo Library reached 88.2% with an excellent category. The correlation analysis result shows a simultaneous relationship between interior design and book collection in terms of visiting interest. Based on this, it is necessary to have an interior design and other book collections so that the library meets visitors' expectations. The visitors' interest is strongly influenced by the interior design and the collection of books. Libraries can improve the interior design by paying attention to aesthetic aspects, economic management, the function of space, the safety of library materials, and the comfort and health of visitors. Book collections are prepared in a varied, relevant, and up-to-date manner with information needs Keywords: Library; design interior; book collection; interests in visiting Abstrak: Penelitian ini bertujuan untuk menguji hubungan antara desain interior, koleksi buku, dan minat kunjung pembaca di perpustakaan perguruan tinggi. Pendekatan penelitian ini mengunakan paradigma kuantitatif dengan metode korelasional. Penelitian ini untuk mengukur hubungan variabel desain interior (X1), koleksi buku perpustakaan (X2), dan minat kunjung pembaca (Y). Populasi berjumlah 2.802 ditarik dalam sampel menjadi 97 melalui teknik multistage sampling. Instrument pegumpulan data, mengunakan observasi, angket, dan dokumentasi. Data penelitian dianalisis menggunakan software SPSS versi 20 guna memberi gambaran korelasi sederhana dan korelasi berganda. Hasil penelitian menunjukkan desain interior Perpustakaan IAIN Palopo tergolong sangat baik (93,4%), koleksi buku berkategori cukup baik (66,7%), dan minat kunjung mahasiswa di Perpustakaan IAIN Palopo mencapai 88,2% dengan kategori sangat baik. Hasil analisis korelasi diketahui terjadi hubungan simultan antara desain interior dan koleksi buku ditinjau dari minat kunjung. Berdasar dari hal itu, perlu adanya rancangan interior dan penambahan koleksi buku agar perpustakaan sesuai dengan harapan pengunjung. Minat kunjung pemustaka sangat dipengaruhi oleh desai interior dan koleksi buku. Perpustakaan dapat memperbaiki desain interior dengan memerhatikan aspek estetika, pengelolaan yang ekonomis, fungsi ruang, dan keamanan bahan pustaka, serta kenyamanan dan kesehatan pengunjung. Koleksi buku dipersiapkan dengan variatif, relevan, dan mutakhir dengan kebutuhan informasi. Kata kunci: perpustakaan; desain interior; koleksi buku; minat kunjung